2020
DOI: 10.1002/ardp.201900269
|View full text |Cite
|
Sign up to set email alerts
|

Propafenone analogue with additional H‐bond acceptor group shows increased inhibitory activity on P‐glycoprotein

Abstract: P‐glycoprotein (P‐gp) is an ATP‐dependent efflux pump that has a marked impact on the absorption, distribution, and excretion of therapeutic drugs. As P‐gp inhibition can result in drug–drug interactions and altered drug bioavailability, identifying molecular properties that are linked to inhibition is of great interest in drug development. In this study, we combined chemical synthesis, in vitro testing, quantitative structure–activity relationship analysis, and docking studies to investigate the role of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This protein is a potential therapeutic target for treating Candida infections because it is responsible for most of the glucanase activity in the Candida cell wall [ 55 ]. Although Actinomycin X 2 and Actinomycin D are similar in chemical structure, Actinomycin D exhibited stronger anti - C. albicans activity due to its six additional H-bonding interactions with 1,3Beta-Glucanase [ 56 ]. Likewise, in the Hamdoon's study, methylated taxifolin demonstrated enhanced binding affinity towards various pro- and antiapoptotic proteins compared to taxifolin, thereby displaying heightened anticancer efficacy [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is a potential therapeutic target for treating Candida infections because it is responsible for most of the glucanase activity in the Candida cell wall [ 55 ]. Although Actinomycin X 2 and Actinomycin D are similar in chemical structure, Actinomycin D exhibited stronger anti - C. albicans activity due to its six additional H-bonding interactions with 1,3Beta-Glucanase [ 56 ]. Likewise, in the Hamdoon's study, methylated taxifolin demonstrated enhanced binding affinity towards various pro- and antiapoptotic proteins compared to taxifolin, thereby displaying heightened anticancer efficacy [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tight junction proteins between the brain capillary endothelial cells are mainly responsible for static barrier properties, resulting in the poor transfer of almost all drugs [6]. Besides, ATP-binding cassette efflux transporter P-glycoprotein play a key role to transport the huge chemotherapeutic agents and hydrophobic compounds outside the brain capillary endothelial cells [7,8]. To overcome this problem, the nanostructure can be used as colloidal drug carriers to enhance the bioavailability of drugs by increasing their diffusion through biological membranes and protect them against enzymes.…”
Section: Introductionmentioning
confidence: 99%